IMPLEMENTASI RECYCLING CLUB SEBAGAI STRATEGI PENDIDIKAN LINGKUNGAN DI SEKOLAH DASAR - Josly Yakob Tintingon; Elni J Usoh; Jeffry Sonny J Lengkong (Jurnal Genta Mulia, 2024)
This article discusses the implementation of the "Recycling Club" program as part of an environmental education strategy in elementary schools. In an effort to increase student awareness of the importance of recycling and sustainable practices, schools have adopted this program. This article provides an overview of the objectives, implementation, and impact of the Recycling Club program in the school environment. This article aims to provide a holistic view of the implementation of the Recycling Club program in elementary schools as a successful environmental education strategy. This program is expected to make a positive contribution to the formation of students who care about the environment from an early age.